2021
DOI: 10.1007/s00125-020-05379-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of infant diet with subsequent obesity at 2–5 years among children exposed to gestational diabetes: the SWIFT study

Abstract: Aims/hypotheses This longitudinal analysis evaluated the independent and joint associations of any breastfeeding (BF) or exclusive BF (EBF) and intake of sugar-sweetened beverages (SSBs) and 100% fruit juice from birth to 1 year with subsequent overweight and obesity among young children exposed to gestational diabetes (GDM). Methods The analysis utilised prospectively collected data from participants enrolled in the Study of Women, Infant Feeding and Type 2 Diabetes after GDM (SWIFT); 1035 pregnant women (20-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…They found that none of the studies observed an effect between the different types of foods introduced and subsequent BMI in childhood except for one prospective study finding a similar association between a later introduction of grains around 8 months of age and lower BMI at 12 months of age [ 44 , 45 ]. Lastly, several studies defined late introduction as early as 4 months of age, not in keeping with the AAP recommendations [ 11 ], which makes it difficult to interpret their overall findings [ 23 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that none of the studies observed an effect between the different types of foods introduced and subsequent BMI in childhood except for one prospective study finding a similar association between a later introduction of grains around 8 months of age and lower BMI at 12 months of age [ 44 , 45 ]. Lastly, several studies defined late introduction as early as 4 months of age, not in keeping with the AAP recommendations [ 11 ], which makes it difficult to interpret their overall findings [ 23 , 46 , 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the benefits of lactation in combination with healthy infant feeding practices for childhood obesity have been well documented. 153 Studies from other cohorts have noted that women with GDM may have reduced breastmilk production as well as different quality breastmilk than women without GDM. 154 Whether the quality of breastmilk among infants with GDM has independent adverse effects on infant growth is not yet established.…”
Section: Lactationmentioning
confidence: 99%
“…T2D was diagnosed via the ADA criteria [32]. Frequency and amount of breastmilk feeding (including expressed breast milk bottle feeding) and formula feeding for each woman were assessed by trained research staff via telephone calls, mailed feeding diaries, questionnaires during in-person visits, and mailed monthly surveys from birth to 12 months post-delivery as previously described [33]. Based on this information, breastfeeding behavior measurements within each month were operationalized as breastfeeding intensity and duration ratio (quantitative methodology), which was calculated as the number of breast milk feeds (on average in 24 h) divided by the total number of all liquid feeds (on average in 24 h) during the past 7 days to yield a score with a range from 0 to 1 as described by Piper et al [34].…”
Section: Design Of Swift Cohortmentioning
confidence: 99%